Young consumers’ intention towards future green purchasing in Malaysia - Shiban, Muhammed Abdullah Sharaf (2014)
Green marketing is all about marketing products that are considered environmentally safe. It involves practicing a lot of activities related to product modification, product packaging, and even advertising. Green marketing also refers to holistic marketing concept in which it involves production, marketing, consumption and product disposal in a way that is less harmful to the environment. The purpose of this study is to examine the influence of price, time, knowledge, satisfaction, eco-label, and social influence on the intention of future green product purchasing among young Malaysian. The measurement of the factors is adopted from past studies for the following variables: price, time, knowledge, satisfaction, eco-label and social influence. The sample size of this study is 250 samples. This study used SPSS 15.0 to analyze the data. The results of this study showed that price, time, and social influence have a relationship with young consumers‟ intention to purchase green products, however knowledge, satisfaction, and eco-label had no influence, discussions of the analysis are provided in the study